Acute toxicity of mosquito pesticides on weed biological control agents in south Florida, USA. Issue 8 (2nd August 2020) - Wheeler, Gregory S.; Lake, Ellen C.; Rayamajhi, Min B.; Smith, Melissa C.
ABSTRACT: Mosquito pesticides effectively control vectors of human disease but have numerous unintended consequences. These may include adversely affecting non-target species such as weed biological control agents. Acute toxicity of two mosquito pesticides, naled and permethrin, was studied on three biological control agents released against invasive weeds in south Florida. These were the biological control agent Oxyops vitiosa of melaleuca, Melaleuca quinquenervia, the agent Neomusotima conspurcatalis for Old World climbing fern, Lygodium microphyllum, and the agent Lilioceris cheni for air potato Dioscorea bulbifera . We calculated LD50 values for both pesticides on early and late instars for each herbivore species. The air potato herbivore, L. cheni was the most sensitive species tested and all three species were more sensitive to the pesticide permethrin than naled. These results indicate that even low concentrations of these products can have a detrimental effect on these weed biological control agents. The unintended consequences of mosquito adulticide applications should be considered when evaluating biological control agent impacts.